The prospects of the African union transitional justice policy 2019 and sustainable peace in Africa (2023)
The African Union (A U) adopted the African Union Transitional Justice Policy (AUTJ Policy) in 2019 against the backdrop of attaining sustainable peace within the African continent. The Policy was designed to serve as a continental guide to member States in the design and implementation of context-specific transitional justice programmes within their respective States. The Policy incorporates indigenous principles and elements which member States should adopt to domesticate transitional justice. Presumably, over the years, the African continent has had the highest number of States confronting conflict situations or repressive regimes. Hence, it would appear that the Policy is a timely intervention of the AU in pursuing its agenda of a peaceable and stable continent. The Policy makes several bold innovations and provisions which are potentially capable of transforming the structure for peace and security in Africa. This study attempts to examine the provisions of the Policy against the conventional narratives of transitional justice principles and mechanisms and the goal of sustainable peace. Is the Policy just another document which will wield little or less significant impact within the continent? The paper adopts a purely doctrinal and desktop review approach in analysing the provisions of the AUTJ Policy within the context of the concept of transitional justice and sustainable peace. The study makes use of data from both primary and secondary sources of law and argues that while the adoption of the Policy is an innovative move, it runs the risk of irrelevance where its provisions are merely recommendatory and elicit no binding obligations from member states.